1998
DOI: 10.1021/jp980977e
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Quenching of Excited Singlet States in a Series of Fluorescamine- Derivatized Nitroxides

Abstract: Steady-state and time-resolved absorption and fluorescence measurements were used to probe the mechanism(s) of excited singlet state quenching by stable nitroxyl radicals in a series of fluorescamine-derivatized nitroxides. Rate constants for intramolecular quenching (k q) acquired from fluorescence lifetime measurements were very high, ranging from ∼0.3 × 1010 s-1 to ≥5 × 1010 s-1, and showed little dependence on solvent polarity. The k q's did not track the values of the Dexter and Förster spectral overlap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 22 publications
(81 reference statements)
0
65
0
Order By: Relevance
“…[1][2][3] Intermolecular quenching may occur through chance collisions between an excited molecule and a nitroxide radical. A tether between the fluorophore and the radical moiety increases encounters between the fluorophore and the radical, which increases the efficacy of fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Intermolecular quenching may occur through chance collisions between an excited molecule and a nitroxide radical. A tether between the fluorophore and the radical moiety increases encounters between the fluorophore and the radical, which increases the efficacy of fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Ac-Tempo does not exert fluorescence from the acridine moiety (Fig. 1B) due to the quenching produced by electron exchange interactions between the Tempo radical and the excited state of acridine (18). The fluorescence quenching of Ac-Tempo can be eliminated upon conversion of the nitroxide moiety into a non-paramagnetic species, e.g.…”
Section: Biochemical Evidence For Selective Interactions Of Ac-tempo mentioning
confidence: 99%
“…Ac-Tempo contains two chemical moieties conjugated by a peptide bond, namely fluorescent acridine and a stable paramagnetic nitroxide radical called Tempo, and, similar to Sphinx, it inherits duality of their physical properties. The nitroxide radical, however, quenches the fluorescence of acridine through an intramolecular intersystem crossing induced by electron exchange (18). We established that the reaction of GS ⅐ radicals with the nitroxide moiety of Ac-Tempo converts it to the corresponding piperidine, which therefore eliminates the quenching to yield a readily measurable fluorescence from acridine moiety and the disappearance of a typical EPR signal from the nitroxide radical.…”
mentioning
confidence: 92%
“…Blough and co-workers have shown that these covalently-linked nitroxidefluorophore adducts can be employed as very sensitive optical sensors of radical/redox reactions (8)(9)(10)(11). Scaiano and co-workers have also developed a number of prefluorescent probes allowing radical and/or antioxidant detection in homogeneous and heterogeneous systems (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%